Proceedings of the Conference on Empirical Methods in Natural Language Processing - EMNLP '08 2008
DOI: 10.3115/1613715.1613809
|View full text |Cite
|
Sign up to set email alerts
|

Predicting success in machine translation

Abstract: The performance of machine translation systems varies greatly depending on the source and target languages involved. Determining the contribution of different characteristics of language pairs on system performance is key to knowing what aspects of machine translation to improve and which are irrelevant. This paper investigates the effect of different explanatory variables on the performance of a phrase-based system for 110 European language pairs. We show that three factors are strong predictors of performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 10 publications
2
53
0
Order By: Relevance
“…We determine the probability of the orientation type for the constituent pairs based on Equation (1). Based on the orientation class for a pair, we consider its score for calculating monotone or swap feature functions and compute F monotone and F swap as shown in Equation (4), where a is the word alignment between S and H, and Aligned(H, Pairs(S), a) shows the aligned covered pairs based on the word alignment a.…”
Section: Integration Into Hpb-smtmentioning
confidence: 99%
See 1 more Smart Citation
“…We determine the probability of the orientation type for the constituent pairs based on Equation (1). Based on the orientation class for a pair, we consider its score for calculating monotone or swap feature functions and compute F monotone and F swap as shown in Equation (4), where a is the word alignment between S and H, and Aligned(H, Pairs(S), a) shows the aligned covered pairs based on the word alignment a.…”
Section: Integration Into Hpb-smtmentioning
confidence: 99%
“…Accordingly, in order to translate a sentence from the source language into the target language, SMT has to handle two problems: (i) finding the appropriate translation of the words in the source sentence ("lexical choice"), and (ii) predicting their correct order in the target sentence ("reordering"). Reordering is one of the most important factors affecting the quality of the final translation [1]. A large amount of research has been conducted to address the reordering problem, much of which follows the discriminative reordering model (DRM), i.e., they consider word reordering as an structured prediction problem and apply a discriminatively trained model to predict the appropriate word order.…”
Section: Introductionmentioning
confidence: 99%
“…We randomly select 40 sentences which have a large amount of reordering (RQuantity (Birch et al 2008) > 1.3) and where the sentence length is between 10 and 40 words.…”
Section: Design and Materialsmentioning
confidence: 99%
“…The word order differences are difficult to model and the amount of reordering has been shown to be a very important predictive factor in translation performance (Birch et al 2008). We argue that research in reordering is hampered by the fact that commonly used automatic metrics do not explicate the reordering performance of machine translation systems.…”
Section: Introductionmentioning
confidence: 98%
“…Automatically identifying such phrases has the potential of improving MT as shown by an oracle study (Mohit and Hwa, 2007). More recent work (Birch et al, 2008) has shown that properties of reordering, source and target language complexity and relatedness can be used to predict translation quality. In information retrieval, the problem of predicting system performance has generated considerable interest and has led to notably good results (Cronen-Townsend et al, 2002;Yom-Tov et al, 2005;Carmel et al, 2006).…”
Section: Introductionmentioning
confidence: 99%